Yusuf Khos Khojib oriental pearl - Hikmatkhon Tursunovna Ahmedova (Zien Journals, 2022)
In the article has analyzed Yusuf Khas Hajib’s «Qutadgu bilig» works and determined his role in the history of oratory and art of speech, including giving them a scientific-theoretical assessment.
Keywords: World Oratory; «Qutadgu Bilig»; preacher